Uczestnictwo w grupach sformalizowanych a rozwój tożsamości we wczesnej adolescencji na przykładzie ZHP = Formal group participation and sense of identity formation during early adolescence (based on Polish Scouts Association) - Hadzicka, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During early adolescence identity formation is the core thread of development. In the same time emerges clear tendency to increasing the role of peer group, fulfilling important role in the life of teenager. Formal groups can have particular impact on their members, because of organizational aspects of functioning, distinguishing them from other peer groups. This paper is an attempt to explain in what ways membership in formal groups can be related to identity formation processes, as an example analysing Polish Scouts Association, and using the dynamic double-cycle model of identity formation (Luyckx et all, 2008).
Keywords: eksploracja; grupa formalna; grupa rówieśnicza; harcerstwo; organizacja; skauting; tożsamość; wczesna adolescencja; zobowiązanie; commitment; early adolescence; exploration; formal group; identity; organization; peer group; scouting; support of development